USE WEBSITE FOR LITERACY SCIENCE: COULD INCREASE SELF-INDEPENDENT LEARNING FOR STUDENTS IN ELEMENTARY SCHOOL? - Febriani, Dewi; Lestari, Ika; Fahrurrozi (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2021)
The digital age in the pandemic requires self-reliance in learning. Toward to train and develop the character of student self-regulated learning, this website presents a media visualization that can support the improvement of feelings of student independence through science literacy activities. This research aims to develop student independence in elementary school used website media that provides content in science literacy activities. The sample of this study is second-grade students from Pondok Kelapa 04 elementary school, East Jakarta, Indonesia, in the 2020/2021 school year. The results showed that a media site is known as Wetracy (Website for Literacy) influenced the development of the character of independence of second-grade students in science literacy activities. Thus, the study concluded that website media could effectively stimulate student’s self-reliance character in science literacy.